2006
DOI: 10.1103/physrevd.73.044033
|View full text |Cite
|
Sign up to set email alerts
|

Fermion localization on thick branes

Abstract: We consider chiral fermion confinement in scalar thick branes, which are known to localize gravity, coupled through a Yukawa term. The conditions for the confinement and their behavior in the thinwall limit are found for various different BPS branes, including double walls and branes interpolating between different AdS5 spacetimes. We show that only one massless chiral mode is localized in all these walls, whenever the wall thickness is keep finite. We also show that, independently of wall's thickness, chiral … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
150
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(155 citation statements)
references
References 27 publications
1
150
0
2
Order By: Relevance
“…In order to localize fermions on a thick brane of the RS-type, one usually needs to introduce some other interactions with background fields besides gravity. One simple interaction in a five-dimensional brane model is the Yukawa coupling between fermions and the background scalar fields [32,43,44,50,54,[61][62][63][64][65][66][67][68][69][70][71][72] when the scalar fields are odd functions of the extra dimension. With this coupling, the shapes of the effective potential of the left-or right-chiral fermion KK mode can be classified as three types: volcano-like [43,63,[65][66][67][68][69], finite square well-like [39,73], and harmonic potentiallike [44,70].…”
Section: Introductionmentioning
confidence: 99%
“…In order to localize fermions on a thick brane of the RS-type, one usually needs to introduce some other interactions with background fields besides gravity. One simple interaction in a five-dimensional brane model is the Yukawa coupling between fermions and the background scalar fields [32,43,44,50,54,[61][62][63][64][65][66][67][68][69][70][71][72] when the scalar fields are odd functions of the extra dimension. With this coupling, the shapes of the effective potential of the left-or right-chiral fermion KK mode can be classified as three types: volcano-like [43,63,[65][66][67][68][69], finite square well-like [39,73], and harmonic potentiallike [44,70].…”
Section: Introductionmentioning
confidence: 99%
“…The trapping of various kinds of matter fields on single or multi branes are also discussed for both thin and thick branes [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Melfo et al studied the localization of fermions on various different scalar thick branes recently [22,23,24], and had shown that only one massless chiral mode is localized in double walls and branes interpolating between different AdS 5 spacetimes whenever the wall thickness is keep finite, while Chiral fermionic modes can not be localized in dS 4 walls embedded in a M 5 spacetime. It is therefore of interest to investigate the possibility that fermion confinement, being directly dependent on the scalar field solution and not only on the spacetime metric, can be affected by the internal structure on the thick brane.…”
Section: Spin 1/2 Fermionic Fieldmentioning
confidence: 99%